ELEMENTAL ANALYSIS OF CZECH WINES INCLUDING WINES FROM ORGANIC PRODUCTION - Slavíková, Zuzana; Pořízka, Jaromír; Diviš, Pavel (SLOVAK UNIV AGRICULTURE NITRA, 2024)
Ensuring the safety of wine as worldwide major beverage commodity is of paramount importance for many control institutions and research groups. This study delves into the elemental composition of Czech wines, with a particular focus on wines from organic production, to comprehensively assess their safety in terms of elemental contaminants. The investigation aims to shed light on potential risks associated with trace elements and heavy metals in wines and to compare these risks between conventionally produced and organically produced wines. The work further focuses on major nutritionally important elements in wine. The aim of this article was screening of elemental composition (Mg, Ca, Cr, Zn, Pb, Cd, Co, Mn, Fe, Cu, Ni, Al, P) of Czech white wines (Moravia region) of different varieties and vintages. Total of 45 samples of different vintage and varieties were analyzed. 35 samples were conventionally produced, 10 samples were produced in the organic production regime. Elemental composition comparison of organic and conventional wines was evaluated. Inductively coupled plasma optical emission spectrometry (ICP-OES) was used for the analysis of wine. Analysis of variance (ANOVA) and principal component analysis (PCA) were used for the data evaluation. Results of this study extended the knowledge about the elemental composition of Czech wines and presents the comparison with wines from different important wine regions. Results showed that Czech wines are not deviating fundamentally from wines from Europe, Australia, and South America in terms of concentration of Mg, Ca, K, P, Zn, Pb, Cd, Co, Mn, Fe, Cu, Ni and Al. Important fact, connected to food safety, is that all tested wines complied with national and European legislation and with OIV limits. Statistically significant differences were found in case of Zn, Ni, Mn, Al, Cd and Mg on significancy level 0.05. Except magnesium, higher concentrations of these metals were found in samples of conventional wines. A more in-depth analysis has attributed these differences to application of synthetic pesticides, for example dithiocarbamate mancozeb.
Keywords: wine; organic wine; elemental analysis; ICP-OES; ANOVA; dithiocarbamate